Pembaruan Informasi Terkini dan Panduan Tentang Pengelolaan Miopia - Nikita Pramesti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction; Myopia, global health, and quality of life problem concerns visual disturbances and the impact of refractive errors on daily life and the morbidity associated with this ametropia. Myopia is a risk factor for vision problems to permanent blindness. Adolescent myopia usually begins in school, and affected individuals typically face a lifelong burden of optical and financial correction for their myopic condition. Purpose: This literature review aims to provide current information and guidance on myopia management. Methods: This research is a literature review study, and the literature used consists of 33 libraries consisting of 3 national journals and 30 international journals. Results: Several studies show myopia can be managed and controlled with more time outdoors. Outdoor activities and atropine eye drops can prevent and control myopia. It is useful for reducing or slowing the progression of myopia including daily low-dose atropine eye drops, in concentrations ranging between 0.01% and 0.05%. Conclusion: Myopia is a refractive error in which light rays entering the eye parallel to the optical axis are refracted into the retina when the ocular accommodation is relaxed.